Anatomical insights into sacrocolpopexy for multicompartment pelvic organ prolapse. Issue 7 (5th July 2015) - Ercoli, Alfredo; Campagna, Giuseppe; Delmas, Vincent; Ferrari, Stefania; Morciano, Andrea; Scambia, Giovanni; Cervigni, Mauro
Abstract : Aims: Pelvic organ prolapse occurs in 50% of parous women. Laparoscopic sacrocolpopexy (LSCP) is a common surgical procedure for restoring pelvic anatomy and function. The aim of this study is to evaluate surgical anatomy and anatomical modifications induced by standardized LSCP. Methods: Ten fresh female cadavers underwent LSCP, six subsequently underwent standard anatomical dissection, and four had sagittal anatomical dissection. Four cadavers were used as control subjects; two of them underwent standard anatomical dissection, and two had sagittal anatomical dissection. Results: Vesicovaginal space dissection resulted in an arrow‐shaped space limited by the trigone and vesical branches of the uterine artery. Rectovaginal space dissection resulted in an inverted V‐shaped space marked by the utero‐sacral and rectovaginal ligaments, the cranial end of the perineal body and the levator ani muscle. Exposing the longitudinal vertebral ligament through a peritoneal and presacral fascia incision along the medial border of the right common iliac artery allowed the identification and the preservation of the right hypogastric nerve. The anterior mesh stretched across the proximal half of the anterior vaginal wall, and the cervix towards the sacral promontory provided excellent cervix suspension and anterior‐vaginal wall support with a concomitant stretch of the pubocervical fascia. The median angle formed by the axis of the infra‐levatorial vagina with the axis of the supra‐levatorial vagina changed from 142° to 171° and determined the linearization‐ventralization of the vaginal canal. Conclusions: LSCP can be performed in a nerve‐sparing, standardized fashion, providing excellent apical suspension and anterior vaginal wall support. Neurourol. Urodynam. 35:813–818, 2016 . © 2015 Wiley Periodicals, Inc.